Do Rankings Reflect Research Quality? - Bruno S. Frey; Katja Rost (Center for Research in Economics, Management and the Arts (CREMA), 2008)
Publication and citation rankings have become major indicators of the scientific worth of universities and countries, and determine to a large extent the career of individual scholars. We argue that such rankings do not effectively measure research quality, which should be the essence of evaluation. For that reason, an alternative ranking is developed as a quality indicator, based on membership on academic editorial boards of professional journals. It turns out that especially the ranking of individual scholars is far from objective. The results differ markedly, depending on whether research quantity or research quality is considered. Even quantity rankings are not objective; two citation rankings, based on different samples, produce entirely different results. It follows that any career decisions based on rankings are dominated by chance and do not reflect research quality. Instead of propagating a ranking based on board membership as the gold standard, we suggest that committees make use of this quality indicator to find members who, in turn, evaluate the research quality of individual scholars.
Keywords: H43; L15; O38; 330; Rankings; Universities; Scholars; Publications; Citations